Resisting the Third Reich: The Catholic Clergy in Hitler’s Berlin, Kevin P. Spicer (DeKalb: Northern Illinois University Press, 2004), 263 pp., cloth 36.00 - Brown-Fleming, Suzanne (Holocaust and genocide studies, 2006)
Serious, nuts-and-bolts studies of German Roman Catholicism under the Third Reich, analyzing the political and historical relationships between Nazi leaders, the German Catholic episcopate, prominent lay Catholics, and key Vatican figures have been published in English since as early as 1962.1 These studies rely largely (though not exclusively) on four general groups of source materials: public sermons, pastoral letters, and religious and secular newspapers; documents generated by Nazi-era government ministries and institutions, including police, legal, and administrative bodies; materials produced by the postwar occupiers; and documents gathered for use in postwar war crimes trials.